سلطات الإدارة في تنفيذ العقد الاداري - الهامل, هناء; بورحلة نور الهدى, نور الهدى (University of Eloued جامعة الوادي, 2022)
ونستخلص في هذا البحث بأن سلطات الإدارة في تنفيذ العقد الإداري، واسعة ومختلفة ومن هذه السلطات؛ حق الإدارة في الرقابة والتوجيه، وسلطة التعديل تنفيذ العقود الإدارية، وكذلك سلطة توقيع الجزاءات الإدارية في تنفيذ العقد. وتعد إحدى الامتيازات الضرورية التي تحتاج إليها الإدارة أثناء حفاظها ورعايتها لتسيير المرافق العامة من جراء تقصير أو إهمال أو إخلال من طرف المتعاقد معها في تنفيذ التزامات التعاقدية، والتي من شأنها التأثير على حسن سير المرافق العامة بانتظام واضطراد. لذلك كان لزوم التصدي لمثل هذه السلطات المتمثلة في سلطات الإدارة الوقائية كسلطة الرقابة والتوجيه، وأيضا سلطة التعديل العقد الإداري، وسلطات الإدارية العقابية كالجزائيات الضاغطة والفاسخة.We conclude in this research that the administration’s powers in implementing the administrative contract are wide and different, and from these powers; The right of management to supervise and direct, and the authority to amend the implementation of administrative contracts, as well as the authority to impose administrative penalties in the implementation of the contract. It is one of the necessary privileges that the administration needs while maintaining and caring for the running of public utilities as a result of negligence, negligence or breach by the contracting party in implementing contractual obligations, which would affect the proper functioning of public utilities regularly and steadily. Therefore, it was necessary to address such authorities represented in the preventive management authorities such as the authority of control and direction, as well as the authority to amend the administrative contract, and the punitive administrative authorities such as the pressing and rescinding penalties.
مذكرة ماستر
Keywords: سلطات الإدارية في تنفيذ العقد الإداري، الغرامة التأخيرية، سلطات العقابية، السلطات الوقائية.; administrative authorities in the implementation of the administrative contract, late fine, punitive authorities, preventive authorities.